Automation of air disinfection and lighting in agricultural buildings - L. Yu. Yuferev; I. M. Dovlatov; E. S. Rudzik (Сельскохозяйственные машины и технологии)
The article describes the urgency of this problem and modern ways of its solving. Modern disinfection and lighting systems are not developed enough. The authors proposed to automate the system of disinfection, dust removal and lighting in the farm building. We developed algorithm on the basis of which the universal program in the programming language C ++ was written. Assembled the microprocessor set ARDUINO. The program is included in the microprocessor ATMEGA, which is part of ARDUINO. As a basis for the disinfection system, a two-component ARUF device was used, which includes two decontaminating components: an ultraviolet lamp and an aerosol dispenser. Each of the algorithms (lighting and disinfection) consists of 3 parts: data collection and analysis, control, data output to the display. The sequence of 3 parts is 1 cycle, then it repeated. In the first part on the basis of indications of sensors assignment to variables of some values was carried out. In the second part, based on the values of the variables, the decontamination and lighting devices are controlled. In the third part due to changing the screen number, variable, it is possible to switch the display and view the status of the installation and external parameters. The program, written on the basis of algorithms, is universal and suitable for almost any poultry and livestock buildings. All parameters (the time of the beginning and completion of the ARUV operation within 24 hours, the daily time of the illumination of a certain cycle, the maximum and minimum humidity, the duration of each cycle) used for control and management are variables. Operator can set the items using the display in the menu.